Identification Of Types of Coral in The Waters of Rutong Island 17 Island Riung Natural Tourism Park - Faisal, Ahmad; Moi, Maria Yasinta; Fitriah, Fitriah (Lembaga Riset Mutiara Akbar, 2023)
Human activities that damage the coral reef ecosistem often accur in the 17 Riung island marine tourism parks, which are one of the torism spots and conservation areas on flores island, Riung district, ngada regency. Based on the resuts of observations and interviews with local residents regarding the existence of rock coral on Rutong island. Coastal communities use it as a limestone dump, it is feared that the coral utilizaton activites carried out by fishermen, if allowed to continue, could damage various existing coral reefs. Based on the problem, reserchers see the need to conduct reserch regarding the presence of coral on Rutong islan of identify types of coral and find out the condition of coral on Rutong island. This research lasted for one month and used survey and line transect methods. Based on the data obtained, if can be concluded that the rock corals in the waters of Rutong island consist of 21 types, namely acropora paniculata, acropora citehera, favites acuticolis, acropora bruegermani, goniostreae retiformis, goniotra pecttinata, cicloseries sp, Ctenactis echinata, Acanthastrea regularies, Seriatopora hikxtriks, Stylopora Sp, Porites chylindra, Goniopora tenuidens, Oulopiillia crispa, Platiygyra sinensis, Fafia spesica, Fafia lizardensis, Pavona variens, Fungia falinae, ollowed by the genus: acropora, acropora, cicloseries, ctenactis, acanthastrea, seriatopora, porites, oulopillia, platygyra, fafia, pavona, fungia